2021
DOI: 10.1115/1.4050912
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Elastomer-Coated Cerclage for Reducing Sternal Cut-Through in High-Risk Patients

Abstract: Background: AISI 316L stainless steel wire cerclage routinely used in sternotomy closure causes lateral cut-through damage and fracture, especially in cases of high-risk patients, which leads to post-operative complications. A biocompatible elastomer (Pellethane®) coating on the standard wire is proposed to mitigate the cut-through effect. Methods: Simplified peri-sternal and trans-sternal, sternum-cerclage contact models are created and statically analyzed in a finite element (FE) software to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Post-sternal complications may occur if the sternal displacement exceeds 2.0 mm [31,32]. Subasi et al [33] numerically analyzed the stress reduction in the cortical bone of the sternum when the steel wire cerclage changed. The numerical simulation results of this study showed that biocompatible elastomer (Pellethane) coating wire is more effective in reducing cortical stress than AISI 316 L stainless steel wire.…”
Section: Wiringmentioning
confidence: 99%
“…Post-sternal complications may occur if the sternal displacement exceeds 2.0 mm [31,32]. Subasi et al [33] numerically analyzed the stress reduction in the cortical bone of the sternum when the steel wire cerclage changed. The numerical simulation results of this study showed that biocompatible elastomer (Pellethane) coating wire is more effective in reducing cortical stress than AISI 316 L stainless steel wire.…”
Section: Wiringmentioning
confidence: 99%